Supervisi Kepala Sekolah untuk Meningkatkan Kinerja Guru PAI di MI Nahdlatul Ulama Pangkalpinang - Apriansyah, Apriansyah; Muhammad Luthfi; Supatmi (UNISAN JURNAL, 2025)
This study aims to describe the implementation of school principal supervision in improving the performance of Islamic Education (PAI) teachers at MI Nahdlatul Ulama, Pangkalpinang City. School principal supervision is an essential managerial function that contributes to improving teaching quality through coaching, mentoring, and evaluating teachers’ performance. This research employs a qualitative approach using a case study design, involving the school principal, PAI teachers, and supporting staff as the main informants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the school principal's supervision includes academic and administrative supervision carried out through supervision planning, classroom observations, and follow-up activities such as coaching and performance evaluation. Academic supervision focuses on enhancing teachers' pedagogical competence, including lesson planning, the use of active learning methods, and classroom management. Meanwhile, administrative supervision relates to the completeness of instructional documents, discipline, and the fulfillment of professional duties. This supervision has a positive impact on improving PAI teachers' performance, as shown by the improved quality of lesson documents, increased teaching method variations, and enhanced teacher professionalism. The study concludes that the school principal’s role as a supervisor is crucial in encouraging the improvement of PAI teacher performance. Structured, planned, and continuous supervision fosters a professional work environment and motivates teachers to enhance their competencies. Therefore, principal supervision serves as a vital instrument in improving the quality of Islamic Education learning in madrasah.